Identification and Characterization of a Novel Hyperthermostable Bifunctional Cellobiohydrolase- Xylanase Enzyme for Synergistic Effect With Commercial Cellulase on Pretreated Wheat Straw Degradation - Han, Chao; Yang, Ruirui; Sun, Yanxu; Liu, Mengyu; Zhou, Lifan; Li, Duochuan (Frontiers in Bioengineering and Biotechnology, 2020)
The novel cellobiohydrolase gene ctcel7 was identified from Chaetomium thermophilum and its recombinant protein CtCel7, a member of glycoside hydrolase family 7, was heterologously expressed in Pichia pastoris and biochemically characterized. Compared with commercial hydrolases, purified CtCel7 exhibited superior bifunctional cellobiohydrolase and xylanase activities against microcrystalline cellulose and xylan, respectively, under optimal conditions of 60°C and pH 4.0. Moreover, CtCel7 displayed remarkable thermostability with over 90% residual activity after heat treatment at 60°C for 180 min. CtCel7 was insensitive to most detected cations and reagents, and preferentially cleaved the β-1,4-glycosidic bond to generate oligosaccharides in continuous saccharification of lignocellulosic substrates, which are crucial for various practical applications. Notably, the hydrolysis effect of the commercial cellulase cocktail on pretreated wheat straw was substantively improved in combination with CtCel7. Taken together, these excellent properties distinguish CtCel7 as a robust candidate for biotechnological production of biofuels and bio-based chemicals.